Anti–programmed death ligand 1 immunotherapies in cancer patients with pre-existing systemic sclerosis: A postmarketed phase IV safety assessment study. (January 2022) - Panhaleux, Marion; Espitia, Olivier; Terrier, Benjamin; Manson, Guillaume; Maria, Alexandre; Humbert, Sébastien; Godbert, Benoît; Perrin, Julie; Achille, Aurélie; Arrondeau, Jennifer; Kostine, Marie; Fallet, Vincent; et al.
Abstract: Objectives: Cancer patients with pre-existing autoimmune disease, such as systemic sclerosis (SSc), are excluded from clinical trials, so the data on tolerability and efficacy of immune checkpoint inhibitors in these patients are limited. This study investigated the tolerability and efficacy of anti–programmed death ligand 1 (PD (L)1) immunotherapies in patients with pre-existing SSc. Methods: Scleronco-01 was a multicentre, nationwide, open-label, phase IV observational study, from 2019 to 2021. Results: Seventeen SSc patients receiving treatment for lung carcinoma (n = 13, 77%), head and neck cancer (n = 2, 12%), melanoma (n = 1, 6%), and colorectal carcinoma (n = 1, 6%) were included. The median (interquartile range) patient age was 60 (34–82) years. Fifteen (88%) patients received anti-PD1 (nivolumab and pembrolizumab) and two (12%) anti-PD-L1 (durvalumab). The median follow-up duration was 12 (range, 2–38) months. Four patients (24%) experienced flare-up of SSc symptoms. Ten patients (59%) developed an immune-related adverse event (grade I–II in 11 patients [65%], grade III–IV in one [6%]) without grade V. The overall response rate was 41% (7/17 patients). The median overall survival was 15.8 (95% confidence interval: 7.3 to not reached) months. Conclusion: Anti-PD1 or PD-L1 immunotherapies are suitable options for cancer patients with pre-existing SSc. Longer follow-up periods are required for long-term safety analyses. Highlights: Immune checkpoint inhibitors can generate immune-related adverse events (irAEs). IrAEs are more frequent in patients with pre-existing autoimmune diseases (AIDs). Systemic Sclerosis (SSc) is an AID associated with cancer. Anti-PD(L)1 immunotherapies are an acceptable anti-cancer treatment for SSc patients.